2017
DOI: 10.1038/s41598-017-02751-8
|View full text |Cite
|
Sign up to set email alerts
|

Node Attribute-enhanced Community Detection in Complex Networks

Abstract: Community detection involves grouping the nodes of a network such that nodes in the same community are more densely connected to each other than to the rest of the network. Previous studies have focused mainly on identifying communities in networks using node connectivity. However, each node in a network may be associated with many attributes. Identifying communities in networks combining node attributes has become increasingly popular in recent years. Most existing methods operate on networks with attributes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 48 publications
0
36
0
Order By: Relevance
“…Due to the profitable application of community detection in plenteous scientific areas, an affluent set of algorithms [2][3][4][5][6][7][8][9][10] has already been published to tackle this a NP-hard class problem. From methods that are exclusively based on the repetitive calculation of a global network topology metric, to alternatives inspired by discrete mathematics and physics, the pluralism of classic community detection processes is indeed remarkable.…”
Section: Classic Community Detection Methods and Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the profitable application of community detection in plenteous scientific areas, an affluent set of algorithms [2][3][4][5][6][7][8][9][10] has already been published to tackle this a NP-hard class problem. From methods that are exclusively based on the repetitive calculation of a global network topology metric, to alternatives inspired by discrete mathematics and physics, the pluralism of classic community detection processes is indeed remarkable.…”
Section: Classic Community Detection Methods and Algorithmsmentioning
confidence: 99%
“…The iterative processes aiming to identify and remove all the inter-connection edges, by recursively maximizing a global topology criterion are classified as divisive algorithms [2,3,[6][7][8]. In these techniques, at each iteration step, a finer community hierarchy layer is formed.…”
Section: Classic Community Detection Methods and Algorithmsmentioning
confidence: 99%
“…Obviously, using only one type of information will ignore another type of information. It has shown that combing network topology with attribute information can not only improve the quality of community detection, but also has potential to provide the semantic descriptions of communities, and help to understand the functions of communities [7][8][9][10][11].Existing methods that joint the two types of information can be roughly classified into two categories: model-based methods [12][13][14][15][16][17][18][19][20][21] and other heuristic methods [22][23][24][25][26][27]. Model-based methods are mainly on the basis of probabilistic generative models.…”
mentioning
confidence: 99%
“…Obviously, using only one type of information will ignore another type of information. It has shown that combing network topology with attribute information can not only improve the quality of community detection, but also has potential to provide the semantic descriptions of communities, and help to understand the functions of communities [7][8][9][10][11].…”
mentioning
confidence: 99%
“…[43,75,146,180,224] and many other papers cited in this survey, topology and semantics often provide complementary information and thus combining them usually leads to achieving better performance in community detection. For example, the semantics may compensate the sparseness of a real network [106]. At the same time, topological information may be helpful if there are missing or noisy attributes [180].…”
mentioning
confidence: 99%